2014
DOI: 10.1002/chem.201403283
|View full text |Cite
|
Sign up to set email alerts
|

Urea‐Induced Acid Amplification: A New Approach for Metal‐Free Insertion Chemistry

Abstract: The enhanced catalytic activity of difluoroboronate ureas proved to be essential as an acidity amplifier to promote metal-free O-H and S-H insertion reactions of α-aryldiazoacetates in high yield. This methodology was found to be generally applicable to a broad substrate scope and presents a conceptually new approach for organocatalytic diazo insertion reactions. Mechanistic investigations suggest that the reaction pathway involves a urea-induced protonation of the α-aryldiazoester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Despite the unclear mode of action of urea catalysis in the context of α-aryl-α-diazo ester activation, excellent yields of both O-H and S-H insertion products were frequently isolated when α-aryl-α-diazo esters were treated with appropriate insertion partners in the presence of just 2.5 mol% of boronate urea catalyst 1 (Scheme 4). 7 Importantly, no reaction was observed if the boronate urea catalyst was omitted while otherwise keeping the reaction conditions identical. In our initial study, a variety of carboxylic acids were found to operate as insertion partners with elec-tron-rich α-aryl-α-diazo esters 5 to afford 6 in high yields.…”
Section: Urea-catalyzed Formal Insertion Reactions Of α-Aryl-α-diazo mentioning
confidence: 99%
“…Despite the unclear mode of action of urea catalysis in the context of α-aryl-α-diazo ester activation, excellent yields of both O-H and S-H insertion products were frequently isolated when α-aryl-α-diazo esters were treated with appropriate insertion partners in the presence of just 2.5 mol% of boronate urea catalyst 1 (Scheme 4). 7 Importantly, no reaction was observed if the boronate urea catalyst was omitted while otherwise keeping the reaction conditions identical. In our initial study, a variety of carboxylic acids were found to operate as insertion partners with elec-tron-rich α-aryl-α-diazo esters 5 to afford 6 in high yields.…”
Section: Urea-catalyzed Formal Insertion Reactions Of α-Aryl-α-diazo mentioning
confidence: 99%
“…The biological and medicinal importance of thioethers , drives the search for convenient and efficient strategies of forming C–S bonds. Several methods are used to synthesize thioethers, including use of acid and base catalysts. Other approaches involve the use of iron­(III) porphyrin catalysts in the addition of disulfides to olefins, , while alternative routes to thioethers include palladium-catalyzed coupling of organic halides with thiols. , Furthermore, thioethers have been produced from copper-catalyzed reactions between diaryl disulfides and β-dicarbonyl compounds . An atom-economic method of forming new C–S bonds is the insertion of the carbene fragment of diazo compounds into the S–H bond of thiols, releasing N 2 as the only byproduct .…”
Section: Introductionmentioning
confidence: 99%
“…The great pharmaceutical potential of this scaffold prompted us to search for new and efficient methods that would provide diversified structures in a minimum number of steps. As a result of their biological importance, many methods for the construction of 3‐oxabicyclo[3.1.0]hexanes have been developed 3‐Oxabicyclo[3.1.0]hexanes can be synthesized by various strategies, such as the Ireland–Claisen rearrangement procedure,, intramolecular cyclization reactions of aryldiazoacetates, Ru‐catalysed annulations, Pd‐promoted [2+1] cycloaddition reactions between dihydrofuran derivatives and alkynes, or Au‐catalysed cyclopropanation reactions of substituted (allyloxy)sulfonium ylides . Another interesting synthetic pathway, reported by Pathak and co‐worker, is based on the formation of single diastereomers of substituted 3‐oxabicyclo[3.1.0]hexanes through the reaction of the corresponding vinyl selenone with nitromethane, malononitrile, and dimethyl malonate in the presence of t BuOK in THF at room temperature .…”
Section: Introductionmentioning
confidence: 99%